PENGARUH PENGGUNAAN MEDIA MINI BOOK PADA MATERI KEBERAGAMAN BUDAYA DI INDONESIA TERHADAP HASIL BELAJAR SISWA SANGGAR BELAJAR KAMPUNG BHARU MALAYSIA - Adiba Dwi Fadya; Ismail Saleh Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the use of mini-book media on the material of cultural diversity in Indonesia on the learning outcomes of students at the Kampung Bharu Malaysia Learning Center. This study is expected to find new insights that can be the basis for better educational policies and learning practices at the elementary level. This type of research is quantitative research with an experimental approach and a one-group pretest-posttest research design. Data collection techniques include observation, tests, and documentation. The subjects in this study were grade 4 with a total of 18 students. Based on the results of the research conducted, it can be concluded that there is an influence of the use of mini-book media on the material of cultural diversity in Indonesia on the learning outcomes of students at the Kampung Bharu Malaysia Learning Center with the results of the t-test obtained a significant value of 0.000 <0.05 so that H0 is rejected and Ha is accepted.